The prevalence of acute kidney injury in women with hypertensive disorders of pregnancy in Africa: a systematic review and meta-analysis - Ekrikpo, Udeme Ekpenyong; Adejumo, Oluseyi A; Akpan, Effiong E; Udo, Aniema I; Nelson, Udeme-Abasi U; Umoh, Idongesit O; Amwaama, Martha J; Edeki, Imuetinyan R; Moussa, Ayman S; Mbah, Ikechukwu O; Okpechi, Ikechi G (African Journal of Nephrology, 2023)
Background: Hypertensive disorder of pregnancy (HDP) is a leading and preventable cause of pregnancy-related acute kidney injury globally. This systematic review and meta-analysis determined the prevalence of AKI in cases of HDP in Africa. Methods: A systematic search of PubMed and African Journals Online (AJOL) was undertaken to identify articles with relevant data published between 1991 and 2022. The pooled prevalence of AKI in women with HDP was determined using meta-analytic techniques. Results: Eighteen eligible articles were included in the systematic review and meta-analysis. The studies included reported on 8 703 pregnant women with HDP with a median age of 27.7 years. Most of the studies were crosssectional and had medium or poor methodological quality. The overall prevalence of AKI was 6.0% (95% CI 3.4–9.3%, I2 = 96.7%; p-value for heterogeneity <0.001). There was no difference in AKI prevalence by African subregion. There was a higher prevalence of AKI in the post-RIFLE era compared to the pre-RIFLE era [7.1% (4.3–10.5%) versus 1.6% (0.5–3.2%); p < 0.001]. The pooled AKI prevalence was higher in the studies that used established AKI consensus criteria than those where criteria were not used [19.6% (10.7–30.3%) versus 4.8 (2.4–8.0%); p = 0.001]. Conclusion: The pooled prevalence of AKI in HDP in Africa was 6.0%. Using consensus AKI definition criteria improves the sensitivity of AKI detection in HDP. The early involvement of nephrologists, as part of a multidisciplinary team taking care of women with HDP, may enhance early AKI detection and reduce the likelihood of renal complications.